(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The experiment to determine the effects of KNO3 and urea in manipulating the harvesting time and increasing yield as well as quality of nine years old mango (Mangifera indica L.) cv. Amrapali plants was carried out at the BAU Germplasm Centre, Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from September 2006 to July 2007. The five treatments included in the experiment were potassium nitrate at 4%, 6% and 8%; urea at 2% and 4% and the control (water spray). Foliar spraying of urea at 4% exhibited better performance in relation to terminal shoot length, number of leaves and leaf area and potassium nitrate at 4% gave superior results with respect to length and breadth of panicle and number of secondary branches per panicle compared to control. The plants sprayed with KNO3 at 4% expressed earlier panicle appearance by 17 days as compared to delayed appearance of panicle in untreated control plants. The plants received KNO3 at 4% produced the highest number of panicles per plant (220.67) whereas the control plants had the least number of panicles (107.67). Regardless of concentration, KNO3 and urea manifested slightly earlier harvest (5 days) compared to control. Plants treated with KNO3 at 4% noted the highest number of fruits per plant (136.67) compared to control (62.67). The treatment urea at 4% resulted in the biggest fruit (202.83g) and the control plants exhibited the smallest fruit (175.00g). Potassium nitrate at 4% gave maximum yield (23.14 kg/plant) as compared to minimum yield (9.12 kg/plant) in the control (water spray). Bangladesh J. Agril. Res. 38(1): 145-154, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15201